Aplikasi Infusa Daun Salam (Syzygium polyanthum) Terhadap Mutu Organoleptik Fillet Ikan Patin (Pangasius sp.) - Arlin Wijayanti; Desy Sasri Untari; Suci Hardina Rahmawati; Muhammad Khoirudin (Jambura Fish Processing Journal, 2026)
Pangasius sp. fillets are highly perishable fishery products that readily undergo quality deterioration during storage due to enzymatic, microbiological, and oxidative activities. The use of natural preservatives, such as Indonesian bay leaf (Syzygium polyanthum), may serve as an alternative approach to maintain fillet quality because this plant contains bioactive compounds with potential antimicrobial and antioxidant properties. This study aimed to analyze the effect of Indonesian bay leaf infusion on the organoleptic quality of Pangasius fillets during chilled storage. The study employed a single-factor Completely Randomized Design with four Indonesian bay leaf infusion concentrations: 0% (P0), 5% (P1), 10% (P2), and 15% (P3) (w/v), with three replications for each treatment. Pangasius fillets were immersed in the infusion for 15 min, drained, and stored at 5±2°C for 7 days. Observations were conducted on days 0, 1, 3, 5, and 7 for color, odor, texture, brightness, and slime using a hedonic test involving 40 untrained panelists. Data were analyzed using analysis of variance, followed by Duncan’s multiple range test at a 95% confidence level. The results showed that Indonesian bay leaf infusion concentration, storage duration, and their interaction significantly affected all organoleptic parameters (p